“ABORTION DATA JUSTICE”: KETIMPANGAN DATA, KRIMINALISASI TERSELUBUNG, DAN INVISIBILITAS PEREMPUAN DALAM STATISTIK KESEHATAN - Lamawatu, Nuril F. (Kantor Wilayah Kementerian Hukum Daerah Istimewa Yogyakarta, 2025)
This paper examines how abortion data within Indonesia’s national health information system fails to reflect social realities and contributes to hidden criminalization and the statistical invisibility of women—further reinforcing structural injustice within the public health system. This study employs a normative legal research method with a qualitative descriptive approach, drawing on literature review and feminist analysis of secondary data and prevailing legal frameworks. The findings reveal that the absence of comprehensive and accurate abortion data in health statistics results in the institutional neglect of women’s experiences, particularly among poor and marginalized groups. Criminalization and stigma are key drivers of data suppression within health facilities, while national survey systems such as the Demographic and Health Survey (SDKI) omit critical variables such as age, reasons for abortion, marital status, and types of service providers. Consequently, the state fails to develop inclusive and evidence-based reproductive health policies. In response, this paper proposes three key recommendations: (a) reformulating abortion data regulations through derivative policies and technical guidelines for service documentation; (b) developing a national survey system and instruments that comprehensively include abortion-related data; and (c) revitalizing legal and ethical education for medical professionals on reproductive rights, legal boundaries, and responsible medical documentation. The concept of abortion data justice is offered as a framework to build an ethical, participatory, and equitable data system for women.